Horde - Aguirre, Ann (2013)
Salvation is surrounded, monsters at the gates, and this time, they're not going away. When Deuce, Fade, Stalker and Tegan set out, the odds are against them.
Keywords: Dystopias -- Juvenile fiction; Survival -- Juvenile fiction; Wilderness survival -- Juvenile fiction; Teenage girls -- Juvenile fiction; Triangles (Interpersonal relations) -- Juvenile fiction; Zombies -- Juvenile fiction; Science fiction -- Juvenile fiction